'Surveying was a kind of writing on the land': The economics of land division as town planning. (November 2020) - Lai, Lawrence WC; Davies, Stephen NG
This article is about the economic role of the primaeval layouts (plats) for a new development area as a conscious act of physical planning. It explains that these foundational layouts of a town or country in the 'new world' were traditionally the work of a surveyor, the impacts of which have been lasting. Typically following a grid iron pattern, with roots in ancient history, the layout of the surveyor may not look attractive. Yet, it has stood the test of time and continued to condition modern development. It serves two significant economic functions. First, it reduces several types of transaction costs, namely, those of competition for land, valuation allocation, identification and subdivision of land as well as revising a layout. Second, it serves to achieve agglomeration, establish a proprietary and common setting and provide vital information as different forms of public good.